Marriage in the Spanish Constitution: a Doctrinal and Case-Law Approach - García-Cuevas Roque, Elena (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2015)
Even knowing that legislators must always apply the most convenient rules to each particular moment in history we can observe a late constant distorted perception of the institution case of study following the change of perception of certain values somehow supported by certain ideological views. Both case and constitutional law have been cautious and moderate trying to study such a controversial issue of social importance without taking any moral or ideological view into consideration. However, they have not reached any common line of action.